Epidemiological, social, and control determinants of Chagas disease in Central America and Mexico - Group discussion - Zeledón, Rodrigo (2007)
The existence of Chagas disease in Central America was reported for the first time in El Salvador in 1913, four years after its discovery in Brazil. At that time only Triatoma dimidiata was known as a vector, but two years later, in the same country, Rhodnius prolixus was discovered, which is a more efficient vector and now considered to be an introduced species in the area. Several epidemiological and clinical studies have shown that, with the exception of Belize, the disease is endemic in all Central American countries and in certain areas has become a serious public health problem. This led the health authorities of the countries to launch the Central American Initiative for the control of Chagas disease in 1997. Since that date, several actions have taken place, aiming to eliminate R. prolixus from the region, lower vectorial transmission by T. dimidiata, and control transmission by blood transfusion.